2023
DOI: 10.1038/s12276-023-00966-6
|View full text |Cite
|
Sign up to set email alerts
|

Defining regorafenib as a senomorphic drug: therapeutic potential in the age-related lung disease emphysema

Abstract: Senescence, a hallmark of aging, is a factor in age-related diseases (ARDs). Therefore, targeting senescence is widely regarded as a practicable method for modulating the effects of aging and ARDs. Here, we report the identification of regorafenib, an inhibitor of multiple receptor tyrosine kinases, as a senescence-attenuating drug. We identified regorafenib by screening an FDA-approved drug library. Treatment with regorafenib at a sublethal dose resulted in effective attenuation of the phenotypes of βPIX knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 67 publications
(87 reference statements)
0
7
0
Order By: Relevance
“…Regorafenib, a well-known inhibitor of multi-receptor tyrosine kinases, is approved for therapy of metastatic colorectal cancer, and is also used as the second-line treatment in patients with hepatocellular carcinoma ( 15 , 16 ). The findings of our previous study demonstrated a therapeutic effect of regorafenib in a PPE-induced animal model of emphysema (which might be in part due to the attenuation of senescence) ( 14 ). In the present study, we asked whether regorafenib has a preventive effect on the development of PPE-induced emphysema in mice.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Regorafenib, a well-known inhibitor of multi-receptor tyrosine kinases, is approved for therapy of metastatic colorectal cancer, and is also used as the second-line treatment in patients with hepatocellular carcinoma ( 15 , 16 ). The findings of our previous study demonstrated a therapeutic effect of regorafenib in a PPE-induced animal model of emphysema (which might be in part due to the attenuation of senescence) ( 14 ). In the present study, we asked whether regorafenib has a preventive effect on the development of PPE-induced emphysema in mice.…”
Section: Resultsmentioning
confidence: 92%
“…In our previous study, regorafenib, a multi-receptor tyrosine kinase inhibitor drug, was identified as a potential senomorphic agent capable of exerting a therapeutic effect in porcine pancreatic elastase (PPE)-induced emphysema in mice ( 14 ). A key element of the experimental setup for that purpose was to administer regorafenib after the development of emphysematous phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our previous study, which demonstrated that silencing beta p21-activated kinase interacting exchange factor (βPIX), a focal adhesion protein, triggers cellular senescence [19], we sought to identify a novel senescence regulator. To this end, we analyzed previous data from tandem mass tag (TMT)-labeling proteomic analysis [20] and found 4643 differentially expressed proteins following βPIX depletion (Fig. 1a and Table S1).…”
Section: Identification Of Frmd6 As a Putative Senescence Regulatormentioning
confidence: 99%
“…Moreover, a recent study by Park et al identified the effectiveness of a sublethal dose of regorafenib in attenuating cellular senescence in human lung fibroblast cells (IMR‐90 cells). Treatment with regorafenib successfully mitigated the βPIX knockdown‐ and doxorubicin‐induced senescence and replicative senescence and reduced SA‐β‐Gal staining and the SASP profile (Park et al, 2023 ). In complementary studies, the potential of regorafenib was shown in a porcine pancreatic elastase (PPE)‐induced model of emphysema.…”
Section: Possible Senotherapeutic Treatments For Copd‐induced Acceler...mentioning
confidence: 99%
“…In complementary studies, the potential of regorafenib was shown in a porcine pancreatic elastase (PPE)‐induced model of emphysema. Treatment with regorafenib (5 mg·kg −1 ) attenuated the senescence profile with reduced SA‐β‐Gal staining and p16 INK4a expression and improved PPE‐induced emphysema in mice (Oh et al, 2023 ; Park et al, 2023 ). To the best of our knowledge, there is no experimental data on the effects of regorafenib on the circadian rhythm in a disease setting.…”
Section: Possible Senotherapeutic Treatments For Copd‐induced Acceler...mentioning
confidence: 99%